Gaya Kepemimpinan, Komunikasi, dan Sumber Daya Manusia yang Mempengaruhi Perkembangan E-Budgeting di Sektor Publik (Studi Kasus pada Badan Keuangan dan Aset Daerah Kota malang) - Yunita, Seri; Maslichah, Maslichah; Fakhriyyah, Dewi Diah (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This research analyzes the influence of leadership style, communication, and human resources on the development of e-budgeting in the public sector at the Regional Finance and Asset Agency (BKAD) of Malang City. This research uses a quantitative approach with a correlational method, and Primary data used in this study is data collected from questionnaires and calculated on a Likert scale. The SPSS program was used to process the data in this study, the sample of this research is employees of BKAD Malang City who were involved in implementing e-budgeting and accounting managers totaling 60 respondents through questionnaires given to BKAD employees in Malang City. The data analysis technique used is multiple linear regression analysis. The results showed that simultaneously, leadership style, communication, and human resources had a positive effect on the development of e-budgeting in BKAD Malang City. Partially, leadership style, communication and human resources each have a positive effect on the development of e- budgeting.Keywords: E-budgeting, leadership style, communication, human resources, public sector.